Single nucleotide polymorphism of AGT rs699 in the pathogenesis of hypertension and ACE inhibitors response: a narrative review - Hartienah, Septiayu Dwi; Ikawati, Muthi'; Zullies Ikawati (Indonesian Journal of Pharmacology and Therapy, 2024)
Hypertension is a chronic cardiovascular disease that affects more than one billion people in the world. Angiotensinogen in the renin-angiotensin-aldosterone system (RAAS) is the main precursor encoded by angiotensinogen (AGT) gene and plays an important role in the development of hypertension. Single nucleotide polymorphism (SNP) of AGT gene is thought related to the pathogenesis of hypertension and angiotensinogen levels in plasma that may affect response to ACE inhibitors. This article reviewed the association of SNP AGT rs699 with the pathogenesis of hypertension and ACE inhibitors response. A total of 14 articles published from 1995 to 2023 were collected from databases including NCBI, Google Scholar, PubMed and Science Direct. Several studies in different populations have been conducted and showed various results. The T allele or TT genotype of AGT rs699 was associated in the pathogenesis of hypertension. However, the association between AGT rs699 and ACE inhibitor response shows inconsistent results, thus further research is needed.